The Kaiserchronik a medieval narrative - Matthews, Alastair, 1980- (Oxford : Oxford University Press, 2012)
A narratological analysis of the Kaiserchronik, or chronicle of the emperors, which provides an account of the Roman and Holy Roman emperors, from the foundation of Rome to the eve of the Second Crusade.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: Kaiserchronik; German poetry -- Middle High German, 1050-1500 -- History and criticism; Court epic, German -- History and criticism